Peningkatan Hasil Belajar Tari melalui Metode Tutor Sebaya di Kelas VIII.1 SMP Muhammadiyah 1 Padang - Efendi, Friska Putri; Astuti, Fuji (TSAQOFAH, 2025)
The instruction of the tari piring (plate dance) in Class VIII.1 at SMP Muhammadiyah 1 Padang continues to face challenges in optimizing students’ understanding and movement skills, particularly among those who are reluctant to ask questions directly to the teacher. This study aims to improve learning outcomes in tari piring through the implementation of the peer tutoring method as a learning strategy. The research employed a Classroom Action Research (Penelitian Tindakan Kelas) method conducted over two instructional cycles involving multiple meetings, with all students in Class VIII.1 as subjects. Data were collected through observation of student activities and documentation of the learning process, then analyzed quantitatively using percentage formulas to assess improvements in learning outcomes. The findings indicate that the peer tutoring method effectively enhances students’ positive engagement, such as attentiveness, willingness to ask questions, and collaboration in group activities. This approach also helped previously struggling students become more actively involved in the learning process. However, the success of this method strongly depends on the teacher’s active role as a guide and facilitator of understanding. Therefore, the combination of peer tutoring and direct teacher guidance has proven to significantly improve the quality of tari piring instruction in Class VIII.1 at SMP Muhammadiyah 1 Padang.